2019
DOI: 10.1136/bcr-2019-230963
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of hypothenar hammer syndrome in a patient with acute ulnar artery occlusion

Abstract: A 56-year-old truck driver with a history of tobacco use presented with acute onset digital ischaemia in the ulnar distribution of his dominant hand, associated with severe pain. Occupational exposures included extensive manual labour and prolonged vibratory stimuli. Workup with Doppler and angiography confirmed the diagnosis of hypothenar hammer syndrome (HHS). After the failure of medical management, he underwent ulnar artery thrombectomy with reconstruction and arterial bypass grafting. His pain improved si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Causes of arterial occlusion, including HHS, can be trauma, embolism and thrombus, arterial malformation, thoracic outlet syndrome and quadrilateral space syndrome (i.e., constriction), medium and small-vessel vasculitis, Raynaud’s disease, antiphospholipid antibody syndrome, myeloproliferative disorders, sclerosis, hypercoagulable states, and immune-mediated/inflammatory disease [ 3 , 4 ]. Miyayama et al reported two patients with heart disease and thrombosis of the upper extremity, which accounted for 19% of the total thrombosis [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Causes of arterial occlusion, including HHS, can be trauma, embolism and thrombus, arterial malformation, thoracic outlet syndrome and quadrilateral space syndrome (i.e., constriction), medium and small-vessel vasculitis, Raynaud’s disease, antiphospholipid antibody syndrome, myeloproliferative disorders, sclerosis, hypercoagulable states, and immune-mediated/inflammatory disease [ 3 , 4 ]. Miyayama et al reported two patients with heart disease and thrombosis of the upper extremity, which accounted for 19% of the total thrombosis [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment for hand ischemia, including HHS, remains unclear. St-Pierre et al summarized possible treatments of hand ischemia from the previous reports [ 3 ]. The first choice of treatment was thrombolytics and anti-platelet drugs within 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Differential diagnosis includes embolic/proximal vascular disease as well as local disease with or without associated systemic disease. Proximal etiologies include cardioembolic causes and large vessel disease such as atherosclerotic plaque and arterial thoracic outlet syndrome [12] . Local etiologies with systemic manifestations include atherosclerotic disease, vasculitis, Raynaud's disease, connective tissue disease.…”
Section: A B C Dmentioning
confidence: 99%